2008
DOI: 10.1007/s11130-008-0079-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes Caused by Genotype and Environmental Conditions in Beta-Glucan Content of Spring Barley for Dietetically Beneficial Human Nutrition

Abstract: Over the 5-year period (2000-2004), a significantly higher beta-glucan content was detected in the waxy varieties Washonubet, Wabet, and Wanubet (6.8-7.6%) and lines formed by crossing these varieties with malting varieties (5.8-7.1%). Conversely, the non-waxy hulled malting-type varieties Kompakt (4.0%) and Krona (4.3%) had significantly lower contents of beta-glucan. The observations also showed that concentrations of beta-glucans in 2000-2004 were significantly affected not only by varieties, but also envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
6
27
0
1
Order By: Relevance
“…The difference in β-glucan content between the hulled and hulless samples shows a tendency towards higher β-glucan content in hulless barley varieties. This is in agreement with results reported by Holtekjølen et al (2006) and Ehrenbergerová et al (2008). Hulless barleys often have high β-glucan contents, and are mainly used as human food because of ease in processing and their edibility (Ferrari et al 2009).…”
Section: Resultssupporting
confidence: 92%
“…The difference in β-glucan content between the hulled and hulless samples shows a tendency towards higher β-glucan content in hulless barley varieties. This is in agreement with results reported by Holtekjølen et al (2006) and Ehrenbergerová et al (2008). Hulless barleys often have high β-glucan contents, and are mainly used as human food because of ease in processing and their edibility (Ferrari et al 2009).…”
Section: Resultssupporting
confidence: 92%
“…Arabinoxylan content was higher in the treated experiment (4.61%) compared Ehrenbergerová et al (2008) and Fleury et al (1997).…”
Section: Resultsmentioning
confidence: 76%
“…Ehrenbergerová et al (2008) described β-glucan content in various barley lines in the range of 4.03-7.57%, Gamlath et al (2008) reported 1.8-6.1% andIzydorczyk andDexter (2008) 3.6-9.7%. Rey et al (2009) reported average β-glucan value of 55 g/kg compared to 35 g/kg for cultivars and lines with nonwaxy starch.…”
Section: Resultsmentioning
confidence: 99%
“…Variabilitu ␤-glukanů i arabinoxylanů významně ovlivňuje genotyp [8,9,10], obsah ␤-glukanů v zrnu ječmene je ovlivňován také hmotností tisíce semen (HTS) a obsahem bílkovin [10].…”
Section:  3 Results and Discussionunclassified